Sistem Pendukung Keputusan Pemilihan Mouse Terbaik untuk Mahasiswa - Mochamad Daffa Rafikri; Perani Rosyani (CV. Multi Kreasi Media, 2025)
The mouse has become one of the essential devices for students in the modern era to complete academic tasks such as typing, graphic design, and programming. However, students often have difficulty finding the right mouse due to the large number of choices with different prices and specifications. The purpose of this study is to create a decision support system (SDM) that can help students choose the best mouse based on five factors: noise when clicking, battery life, ergonomics, compatibility with operating systems, and price. The three Multi Criteria Decision Making (MCDM) methods used in this system are Simple Additive Weighting (SAW), Weighted Product (WP), and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The results showed that the TOPSIS method recommended the HP X200 Wireless Mouse, while the SAW and WP methods recommended the Logitech M331 SilentPlus. These different results indicate that each method uses different approaches and features to perform calculations. This web-based system uses PHP and MySQL and is designed to provide honest and clear recommendation results without requiring user login. It is hoped that with this system, students will get the right guidance to choose a mouse that suits their academic needs.